2014
DOI: 10.1371/journal.pone.0112364
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gain-Of-Function Mutation of the Proneural IRX1 and IRX2 Genes Disrupts Axis Elongation in the Araucana Rumpless Chicken

Abstract: Axis elongation of the vertebrate embryo involves the generation of cell lineages from posterior progenitor populations. We investigated the molecular mechanism governing axis elongation in vertebrates using the Araucana rumpless chicken. Araucana embryos exhibit a defect in axis elongation, failing to form the terminal somites and concomitant free caudal vertebrae, pygostyle, and associated tissues of the tail. Through whole genome sequencing of six Araucana we have identified a critical 130 kb region, contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 88 publications
5
26
1
1
Order By: Relevance
“…The phalloidin and hematoxylin data show that progressively smaller somites form towards the tail tip, and they all form discretely with no evidence of segregation anomalies, including segregation of the most distal somite from posterior mesoderm. This data complements several other studies that show that when somite addition has ceased, undifferentiated mesenchyme remains at the tail tip, distal from the last separate somite, which then undergoes apoptosis 9,23,24 . Our study and those previously reported demonstrate that even the most distal somite segregates, and that all distal somites form discretely.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The phalloidin and hematoxylin data show that progressively smaller somites form towards the tail tip, and they all form discretely with no evidence of segregation anomalies, including segregation of the most distal somite from posterior mesoderm. This data complements several other studies that show that when somite addition has ceased, undifferentiated mesenchyme remains at the tail tip, distal from the last separate somite, which then undergoes apoptosis 9,23,24 . Our study and those previously reported demonstrate that even the most distal somite segregates, and that all distal somites form discretely.…”
Section: Resultssupporting
confidence: 90%
“…Immunostaining showed that both taper distally, in proportion to the tail profile, and extend to the tail tip. While excess neural differentiation and defects in notochord patterning can cause short and/or fused tails 8,9 , there is no morphological evidence of such events in wildtype chicken development.…”
Section: Development Of Structures In the Pygostyle And Free Vertebramentioning
confidence: 99%
See 1 more Smart Citation
“…There is now strong evidence from several vertebrate species that paraxial mesoderm continues to be generated from bipotential neuromesodermal progenitors (NMPs) throughout the entire course of somite formation and axis extension (Fig. 1A, B) [3][4][5][6][7][8][9]. During commitment to 3 the mesodermal lineage from NMPs, cells exist in a niche (also referred to as the mesodermal maturation zone) that has defined molecular and cellular properties ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work demonstrated that the caudalmost progenitors within the tailbud, the posterior wall progenitor cells (PWPCs; sometimes referred to as neuromesodermal progenitors), are bipotential and continuously make neural/mesodermal fate decisions during embryo elongation. (Freese et al, 2014;Garriock et al, 2015;Gentsch et al, 2013;Gouti et al, 2014;Kondoh and Takemoto, 2012;Martin and Kimelman, 2012;Tzouanacou et al, 2009). These cells give rise to the growing spinal cord, somites and vasculature.…”
Section: Introductionmentioning
confidence: 99%